Permanent Single-Line-to-Ground Fault Removal Method for Ferro-Resonance Avoidance in Neutral Ungrounded Distribution Network - Pan Lu; Wen Wang; Qian Yu; Bishuang Fan; Pengfei Liu; Faliang Wang; Xiangjun Zeng (IEEE Access, 2022)
In the neutral ungrounded distribution network, the removal of permanent single-line-to-ground (SLG) fault easily leads to saturation of the electromagnetic voltage transformers (PT), which may cause ferroresonance overvoltage and PT failure. This paper analyzes the zero-sequence voltage after the removal of the SLG fault and reveals the mechanism of ferroresonance excited by the removal of the SLG fault. Then, the total power and transient energy of the zero-sequence circuit under the SLG fault are analyzed. It is deduced that the energy reaches the minimum value at the zero-cross point (ZCP) of the neutral voltage. Based on this, a permanent SLG fault removal method to avoid ferroresonance is proposed, which uses the ZCP point as the fault removal instant. Simulations in ATP-EMTP show that the proposed method can effectively avoid ferroresonance on subharmonic mode. It can also enhance the ferroresonance suppression performance of the ferroresonance suppression resistor in the fundamental-frequency and high-frequency conditions.